An analysis of feminism in the movie â€œThe Hunting Groundâ€ reviewed from the semiotics of John Viske - Fabianti, Rachmi Herdini; Putra, Fajar Dwi (COMMICAST, 2021)
The Hunting Groundâ€ is a documentary movie which tells about the sexual violence in United States colleges. The story is about the new college students, especially women who became the targets of rape and sexual violence. It is a pity because the colleges always ignore and do not respond the report from the victims. The aim of this study is to determine the representation of feminism in the "The Hunting Ground" movie through John Fiske's semiotics. This research used qualitative method with the semiotics analysis of John Fiske. The Object of this research is the cases of feminism which is contained in this movie with The Codes of Television theory. This theory use three social codes such as reality, representation, and ideology. The result of this research were: First, the forming of feminism meaning in â€œThe Hunting Groundâ€ movie was through dialogues, interviews, narratives, and conflicts which was shown from the process of the survivors' struggle to get their welfare back. Second, the feminism in â€œThe Hunting Groundâ€ movie was shown through the behaviors and attitudes of survivors who dared to oppose their own colleges by filing lawsuits and accusations on the cases which befell the victims. Third, the formation of liberal feminism was a movement which described the situation.